1996
DOI: 10.1289/ehp.961041319
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human topoisomerase II in vitro by bioactive benzene metabolites.

Abstract: Benzene is a clastogenic and carcinogenic agent that induces acute myelogenous leukemia in humans and multiple types of tumors in animals. Previous research has indicated that benzene must first be metabolized to one or more bioactive species to exert its myelotoxic and genotoxic effects. To better understand the possible role of individual benzene metabolites in the leukemogenic process, as well as to further investigate inhibition of topoisomerase 11 by benzene metabolites, a series of known and putative ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“…Some of the cytogenetic abnormalities observed (e.g., long arm deletions of chromosomes 5 and 7, aneuploidy in chromosomes 8 and 21) are similar to those observed in patients with secondary leukemias induced by alkylating agents and topoisomerase II inhibitor chemotherapy drugs [van Leeuwen, 1996;Felix, 1998], and by persons developing solvent-induced leukemias [Crane et al, 1996;Davico et al, 1998]. Several activated benzene metabolites (including phenol, 4,4 H -biphenol, 2,2 H -biphenol, hydroquinone, catechol, 1,2,4-benzenetriol, 1,4-benzenequinone, and trans-trans-muconaldehyde) have been shown to inhibit topoisomerase II, an enzyme critical in DNA replication and repair [Chen and Eastmond, 1995;Frantz et al, 1996;Eastmond et al, 2000]. Studies in animals and humans have shown that benzene induces deletions and other large-scale chromosomal alterations [Schiestl et al, 1997;Zhang et al, 1998;Eastmond et al, 2000], translocations [Aksoy, 1988;Chen et al, 1994;Eastmond et al, 2000], and aneuploidy [Chen et al, 1994;Zhang et al, 1996;Zhang et al, 1998].…”
Section: Cytogenetic Effects Of Benzene and Its Metabolitesmentioning
confidence: 99%
“…Some of the cytogenetic abnormalities observed (e.g., long arm deletions of chromosomes 5 and 7, aneuploidy in chromosomes 8 and 21) are similar to those observed in patients with secondary leukemias induced by alkylating agents and topoisomerase II inhibitor chemotherapy drugs [van Leeuwen, 1996;Felix, 1998], and by persons developing solvent-induced leukemias [Crane et al, 1996;Davico et al, 1998]. Several activated benzene metabolites (including phenol, 4,4 H -biphenol, 2,2 H -biphenol, hydroquinone, catechol, 1,2,4-benzenetriol, 1,4-benzenequinone, and trans-trans-muconaldehyde) have been shown to inhibit topoisomerase II, an enzyme critical in DNA replication and repair [Chen and Eastmond, 1995;Frantz et al, 1996;Eastmond et al, 2000]. Studies in animals and humans have shown that benzene induces deletions and other large-scale chromosomal alterations [Schiestl et al, 1997;Zhang et al, 1998;Eastmond et al, 2000], translocations [Aksoy, 1988;Chen et al, 1994;Eastmond et al, 2000], and aneuploidy [Chen et al, 1994;Zhang et al, 1996;Zhang et al, 1998].…”
Section: Cytogenetic Effects Of Benzene and Its Metabolitesmentioning
confidence: 99%
“…The quinone-based topoisomerase II poisons differ from "classic" topoisomerase II poisons (such as etoposide and bioflavonoids) in two ways. First, quinones are mixed-function inhibitors of the type II enzyme: they increase DNA scission when added to a topoisomerase II-DNA complex, but inhibit scission when incubated with the enzyme prior to the addition of nucleic acids (36)(37)(38)(39)(50)(51)(52)(53)(54). Second, in contrast to compounds like etoposide (which interact with topoisomerase II in a non-covalent manner), quinones act by covalently attaching to the protein (35)(36)(37)(38)(39)53).…”
mentioning
confidence: 99%
“…Using an antikinetochore antibody-based micronucleus assay and FISH techniques in HL-60 cells, BT was found to produce mainly aneugenic effects by disrupting microtubules [13,14]. Moreover, in vitro inhibition of enzymes involved in DNA replication and repair, as topoisomerase enzymes, by BT and other benzene metabolites represents a potential mechanism for the formation of chromosomal aberrations and may contribute to the leukemogenic effect of benzene [43,44].…”
Section: Discussionmentioning
confidence: 99%